Safety and health assessment of corrosion inhibitors using an index-based methodology / Siti Rafidah Ab Rashid, Mohamad Khairul Anwar Mohamad Rasidin and Nor Roslina Rosli - Ab Rashid, Siti Rafidah; Mohamad Rasidin, Mohamad Khairul Anwar; Rosli, Nor Roslina (Universiti Teknologi MARA, 2023)
Corrosion inhibitors are extensively used for the protection of materials against corrosion due to their simplicity in application. Despite the advantage, many corrosion inhibitors contain organic compounds that pose toxicity concerns. This study focused on the assessment of the safety and health risks associated with the usage of various types of corrosion inhibitors using an index-based methodology. The analysis focused on the toxicity of corrosion inhibitors and their influences on the environment. The outcome presents a set of criteria for choosing commonly used corrosion inhibitors. This case study evaluated five different types of corrosion inhibitors, namely sodium molybdate, sodium bisulfite, potassium silicate, phosphate ester, and dicyclohexylamine nitrite. Based on the results of the safety sub-index, sodium molybdate and potassium silicate were the safest corrosion inhibitors based on their scores of zero for both flammability and chemical reactivity. However, the results from the health sub-index revealed that sodium molybdate was the only safest corrosion inhibitor. It can be concluded that the systematic nature of the indexbased assessment could provide a useful method of analysing a wide varitety of chemical substances from industrial applications to household items.